(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:Some critics study aesthetic transformations by adopting a set of foundations on which the artistic work is built, as the reliance in this method is not on the historical sequence of philosophical ideas, but rather finding formative and intentional commonalities, and organizing philosophical ideas according to them, which provides the possibility of identifying the general foundations Which centered around most of the aesthetic philosophical theories, where the research problem came to impose the following question (: Is it possible to achieve the emotional theory and its reflections in the designs of modern fabrics?). The research also focused on the concept of emotional theory and emotional theory and its preoccupations in the romantic school. The emotional theory and its reflections in women’s textile designs were also discussed. And then the design methods of designing the women’s cloth, and then the theoretical framework indicators. The third topic came the research procedures and then the results of the research and the most important conclusions and a list of sources.key words :Emotional theory, reflection, textile design, modernity